Viruses in saliva from sanctuary chimpanzees (Pan troglodytes) in Republic of Congo and Uganda - Dunay, Emily; Rukundo, Joshua; Atencia, Rebeca; Cole, Megan F; Cantwell, Averill; Emery Thompson, Melissa; Rosati, Alexandra G; Goldberg, Tony L (Public Library of Science, 2023)
Pathogen surveillance for great ape health monitoring has typically been performed on non-invasive samples, primarily feces, in wild apes and blood in sanctuary-housed apes. However, many important primate pathogens, including known zoonoses, are shed in saliva and transmitted via oral fluids. Using metagenomic methods, we identified viruses in saliva samples from 46 wild-born, sanctuary-housed chimpanzees at two African sanctuaries in Republic of Congo and Uganda. In total, we identified 20 viruses. All but one, an unclassified CRESS DNA virus, are classified in five families: Circoviridae, Herpesviridae, Papillomaviridae, Picobirnaviridae, and Retroviridae. Overall, viral prevalence ranged from 4.2% to 87.5%. Many of these viruses are ubiquitous in primates and known to replicate in the oral cavity (simian foamy viruses, Retroviridae; a cytomegalovirus and lymphocryptovirus; Herpesviridae; and alpha and gamma papillomaviruses, Papillomaviridae). None of the viruses identified have been shown to cause disease in chimpanzees or, to our knowledge, in humans. These data suggest that the risk of zoonotic viral disease from chimpanzee oral fluids in sanctuaries may be lower than commonly assumed.